2018
DOI: 10.1186/s12885-018-5068-0
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility, acceptability and outcomes of exergaming among individuals with cancer: a systematic review

Abstract: BackgroundIndividuals with cancer have reduced quality of life, functionality, range of motion, strength, and an increase in pain and fatigue. Exergaming appears to be an effective rehabilitation tool for Parkinson’s disease, multiple sclerosis and post-stroke patients to improve functionality, balance and quality of life; however, the usefulness of exergaming in individuals with cancer is unknown. The aim of this systematic review is to describe exergaming interventions delivered to adults with a current or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 73 publications
5
21
1
1
Order By: Relevance
“…This systematic review includes eight studies, comprising 195 patients, 89 COPD [41, 45, 46, 48, 51], 39 cancer patients [51], 43 cancer survivors [55], and 24 patients with HF [53]. Mendoza et al recruited COPD patients with both I, II, III, and IV GOLD 2011 [56] classification [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review includes eight studies, comprising 195 patients, 89 COPD [41, 45, 46, 48, 51], 39 cancer patients [51], 43 cancer survivors [55], and 24 patients with HF [53]. Mendoza et al recruited COPD patients with both I, II, III, and IV GOLD 2011 [56] classification [49].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, human interface technology can reduce the gap between therapists and patients, who may feel more responsible to adhere when directly supervised [44]. Furthermore, technology tools offer the possibility for a more enjoyable and motivational approach to PA programs (e.g., exergaming) [44, 45]. Taken together, this evidence suggests the high potential of the monitoring and user-interface technology in promoting an active lifestyle in persons with disabilities and chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization’s “Rehabilitation 2030” campaign launched in 2017 pointed out that rehabilitation programs should follow a holistic approach for chronic disease management, optimize independence, and prolong community engagement [ 75 ]. Because it is inexpensive [ 49 ], safe [ 55 , 56 ], and easy to use [ 53 ], exergaming can be performed unsupervised even for community-dwelling healthy older adults [ 76 , 77 ]. Exergaming interventions are gradually being used as a physical cognitive rehabilitation tool for elderly people with mild cognitive impairment or dementia living at home in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Exergames have been gradually implemented in rehabilitation [ 37 , 38 ], education [ 39 ], and other fields [ 40 ], and have been widely accepted by a range of populations from children [ 41 , 42 ] to the elderly [ 43 , 44 ]; moreover, positive results were found for individuals with various diseases such as dementia [ 45 ], stroke [ 46 ], Parkinson disease [ 34 ], multiple sclerosis [ 47 ], cystic fibrosis [ 48 ], and cancer [ 49 ]. Recent studies have demonstrated the feasibility, acceptability, and effectiveness of exergaming in improving physical functions such as gait and balance [ 50 ], motion control [ 51 ], and exercise capacity [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fantasy is one lever to attract and motivate people to exercise. The ability of exergames to attract audience have been shown in some studies [6]; however, the point is to maintain mid-and long-term interest. In order to improve the retention rate, some studies use fantasy and combine physical activity with gaming to make physical exercise fun.…”
Section: Related Workmentioning
confidence: 99%